HISGO (HISTORY GOVERNMENT): MEDIA PEMBELAJARAN SEJARAH BERBASIS VIRTUAL REALITY PADA PEMBELAJARAN STEM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SMA - Novitasari, Ulfa; Maskun, Maskun; Sumargono, Sumargono; Pratama, Rinaldo Adi (STKIP Pesisir Selatan, 2025)
The purpose of this study is to develop a history learning media integrated with science and technology, especially by implementing the STEM (Science, Technology, Engineering, and Mathematics) approach. One form of learning media innovation developed in this study is Virtual Reality (VR)-based media, which aims to improve students' critical thinking skills. This study uses the Research and Development (R&D) method with a 4D development model, which consists of four stages: 1) analysis stage, 2) design stage, 3) development stage, 4) implementation stage, and added stage 5) evaluation to measure the success of implementation. The research subjects involved students of class XII IPS 1 as the experimental class and XII IPS 2 as the control class at SMA Negeri 4 Bandar Lampung. The type of research used is a quasi-experiment with a pretest-posttest design. After the treatment was given to the experimental class through the use of VR-based HISGO media, the results of the analysis using the SPSS 24 application showed a significance value of 0.000 <0.05. This indicates a significant difference between the learning outcomes of the experimental class and the control class. Thus, this learning media is proven to be effective in improving students' critical thinking skills.